-8-4=x+7-2x

Simple and best practice solution for -8-4=x+7-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8-4=x+7-2x equation:


-8-4=x+7-2x

We simplify the equation to the form, which is simple to understand
-8-4=x+7-2x

We move all terms containing x to the left and all other terms to the right.
-1x+2x=+7+8+4

We simplify left and right side of the equation.
+1x=+19

We divide both sides of the equation by 1 to get x.
x=19

See similar equations:

| 9b^2-80b-20=0 | | 27-(x+9)=9x-2 | | 9*b^2-20=80b | | (2x^2)3=8x^5 | | 11x+5y=7 | | 4u=76 | | x^2+y^2-6y+5=0 | | 15-y=185 | | 9ln(3x)=72 | | 23=-x | | X^2-14x=2 | | 2x+-1=3 | | 2(l+w)=p | | 8x+20=.5(15x+10) | | (4x+3)(x+7)=0 | | 3(-4b)+7b=-15 | | 14+2y=4 | | 14x+2y=4 | | 5x+2(4x)=26 | | -4=5(-8x) | | 20-b-3b+5=1 | | 2(5x)=20 | | -x^2+6x+120=0 | | 5y-3x=-62 | | 14x-15-13x-7=9 | | 3x-7=68 | | 2y+y+9y=240 | | x+24=51 | | 6+2x=46 | | 28=x-34 | | (3x-4)(2x-3d)=(2x-3d)(2x-4d) | | t=2t+3 |

Equations solver categories